Palladium- and ruthenium-catalyzed cycloisomerization of enynamides and enynhydrazides: a rapid approach to diverse azacyclic frameworks. - Walker, P; Campbell, C; Suleman, A; Carr, G; Anderson, E (2013)
I want to ride my azacycle: The title reaction of enynamides affords a wide diversity of azacycles. The reactions are high-yielding, highly stereoselective, and proceed rapidly under mild reaction conditions. Equivalent transformations using enynhydrazides offer new routes to pyrazole and indazole scaffolds. Boc=tert-butoxycarbonyl, EWG=electron-withdrawing group, Ns=4-nitrobenzenesulfonyl, Ts=4-toluenesulfonyl. Copyright © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.